Kinetics of singlet oxygen photosensitization in human skin fibroblasts - Jiménez-Banzo, Ana; Sagristà, M. Luisa; Mora, Margarita; Nonell, Santi (Free radical biology & medicine, 2008)
The roles played by singlet oxygen ( 1O 2) in photodynamic therapy are not fully understood yet. In particular, the mobility of 1O 2 within cells has been a subject of debate for the last two decades. In this work, we report on the kinetics of 1O 2 formation, diffusion, and decay in human skin fibroblasts. 1O 2 has been photosensitized by two water-soluble porphyrins targeting different subcellular organelles, namely the nucleus and lysosomes, respectively. By recording the time-resolved near-IR phosphorescence of 1O 2 and that of its precursor the photosensitizer's triplet state, we find that the kinetics of singlet oxygen formation and decay are strongly dependent on the site of generation. 1O 2 photosensitized in the nucleus is able to escape out of the cells while 1O 2 photosensitized in the lysosomes is not. Despite showing a lifetime in the microsecond time domain, 1O 2 decay is largely governed by interactions with the biomolecules within the organelle where it is produced. This observation may reconcile earlier views that singlet oxygen-induced photodamage is highly localized, while its lifetime is long enough to diffuse over long distances within the cells.